2011
DOI: 10.1162/jocn_a_00110
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Oscillatory Dynamics Predict Feedback Learning and Action Adjustment

Abstract: Abstract■ Frontal oscillatory dynamics in the theta (4-8 Hz) and beta (20-30 Hz) frequency bands have been implicated in cognitive control processes. Here we investigated the changes in coordinated activity within and between frontal brain areas during feedback-based response learning. In a time estimation task, participants learned to press a button after specific, randomly selected time intervals (300-2000 msec) using the feedback after each button press (correct, too fast, too slow). Consistent with previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
144
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(173 citation statements)
references
References 60 publications
26
144
2
1
Order By: Relevance
“…These results are therefore consistent with the idea that right frontal theta oscillations are important for coordinating different brain regions across different frequency bands during action monitoring and cognitive control throughout task performance (Cavanagh et al, 2009;Cohen, 2011;Gevins et al, 1997;Igarashi et al, 2013;Ishii et al, 1999;Jensen and Tesche, 2002;Mizuhara and Yamaguchi, 2007;Sauseng et al, 2010;van de Vijver et al, 2011). Conversely, for "go" responses, no frontal theta peak sources were found and only minimal theta activity (using peak locations from other response types) were observedconsistent with the hypothesis that prepotent responding is driven by Type 1 automatic processes with minimal action monitoring and cognitive control required.…”
Section: Frontal Theta Oscillationssupporting
confidence: 87%
“…These results are therefore consistent with the idea that right frontal theta oscillations are important for coordinating different brain regions across different frequency bands during action monitoring and cognitive control throughout task performance (Cavanagh et al, 2009;Cohen, 2011;Gevins et al, 1997;Igarashi et al, 2013;Ishii et al, 1999;Jensen and Tesche, 2002;Mizuhara and Yamaguchi, 2007;Sauseng et al, 2010;van de Vijver et al, 2011). Conversely, for "go" responses, no frontal theta peak sources were found and only minimal theta activity (using peak locations from other response types) were observedconsistent with the hypothesis that prepotent responding is driven by Type 1 automatic processes with minimal action monitoring and cognitive control required.…”
Section: Frontal Theta Oscillationssupporting
confidence: 87%
“…In this sense, it has been proposed that medial frontal theta activity represents the broad coordination of several brain regions implicated in action monitoring and control processes (Cavanagh et al, 2010). Accordingly, theta power increases seem to be relevant for task switching (Cunillera et al, 2012), for improving learning (van de Vijver et al, 2011), and for future behavioral adjustments (Cavanagh, Cohen, & Allen, 2009;Cavanagh et al, 2010;Womelsdorf et al, 2010).…”
Section: Consummatory Responses To Monetary Rewards In Anhedoniamentioning
confidence: 99%
“…Accordingly, these signals in the mPFC might help the organism to detect potential cognitive conflicts arising from previous expectations and unexpected outcomes, enhancing action monitoring and control processes (Botvinick, Cohen, & Carter, 2004;Holroyd & Coles, 2002;Ridderinkhof, Ullsperger, Crone, & Nieuwenhuis, 2004). In this regard, it has been proposed that increases of the medial-frontal theta component may represent a general top-down mechanism operating over expectation violation and behavioral adaptation in order to improve performance and learning (Cavanagh et al, 2010;Cunillera et al, 2012;Tzur & Berger, 2009;van de Vijver, Ridderinkhof, & Cohen, 2011;Womelsdorf, Johnston, Vinck, & Everling, 2010).…”
mentioning
confidence: 99%
“…Beta oscillations upon reward delivery have been related to improved learning of stimulus materials or task contingencies (i.e., reinforcement learning; Cohen, Elger, and Ranganath 2007); the increase in beta band oscillations following positive reinforcement has been suggested to function as a mechanism to strengthen the current representations of value and reward, thereby influencing future behavior (Van de Vijver, Ridderinkhof, and Cohen 2011). Indeed, beta oscillations following reward delivery have been found to be predictive of improved memory performance for the rewarded stimuli (Kawasaki and Yamaguchi 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that medial-frontal EEG oscillations (regular cyclic voltage changes) in the beta frequency range (12-30 Hz;Cohen, Elger, and Ranganath 2007;HajiHosseini, Rodríguez-Fornells, and Marco-Pallarés 2012;Kawasaki and Yamaguchi 2013;Marco-Pallares et al 2008;Van de Vijver, Ridderinkhof, and Cohen 2011) are associated with reward processing, while lower frequencies (most prominently theta, 4-8 Hz) are more related to losses and other negative outcomes (Cavanagh, Cohen, and Allen 2009;Cavanagh et al 2010;Cohen, Elger, and Ranganath 2007;Marco-Pallares et al 2008;Van de Vijver, Ridderinkhof, and Cohen 2011). Indeed, Lucchiari and Pravettoni (2012) recently observed that beta activity seems to be modulated by the experience of pleasure associated with a favorite brand, whereas theta modulation seems to reflect the lack of this experience.…”
Section: Brain Responses To Movie Trailers Predict Individual Preferementioning
confidence: 99%